Corn Gluten Feed for Beef Cattle - Bob Myer; Matt Hersom (EDIS)
AN-201, a 4-page fact sheet by Bob Myer and Matt Hersom, provides beef cattle producers with basic information about this co-product of wet-corn milling industry that is readily available in the southeastern USA — utilization, considerations for use, and feeding guidelines. Includes references and a table of typical nutrient composition of corn gluten feed (CGF). Published by the UF Department of Animal Science, April 2008.